Bloodmeal Analysis Reveals Avian Plasmodium Infections and Broad Host Preferences of Culicoides (Diptera: Ceratopogonidae) Vectors - Santiago-Alarcon, Diego; Havelka, Peter; Schaefer, Hinrich Martin; Segelbacher, Gernot (PloS one, 2012)
Changing environmental conditions and human encroachment on natural habitats bring human populations closer to novel sources of parasites, which might then develop into new emerging diseases. Diseases transmitted by host generalist vectors are of special interest due to their capacity to move pathogens into novel hosts. We hypothesize that humans using forests for recreation are exposed to a broad range of parasites from wild animals and their vectors. A corollary of this is that new vector-host, parasite-host, and vector-parasite associations could eventually develop. Thus, we expect to observe atypical vector-host associations. Using molecular bloodmeal analysis via amplification of the mtDNA COI gene we identified the vertebrate hosts of Culicoides (Diptera: Ceratopogonidae) species in a sub-urban forest of Southwestern Germany. Bloodmeals were also checked for haemosporidian infections by amplifying a fragment of the mtDNA cyt b gene. We identified a total of 20 Culicoides species, thirteen of which fed on humans. From 105 screened bloodmeals we obtained high quality sequences for 77 samples, 73 (94.8%) originated from humans, two from livestock (Bos taurus and Equus caballus), and two from wild birds (Sylvia atricapilla and Turdus merula). We found that four Culicoides species previously assumed to feed exclusively on either birds (C. kibunensis) or domestic mammals (C. chiopterus, C. deltus, C. scoticus) fed also on humans. A total of six Culicoides abdomens were infected with avian haemosporidian parasites (Plasmodium or Haemoproteus), four of those abdomens contained blood derived from humans. Our results suggest that parasites of wild animals may be transferred to humans through infectious bites of Culicoides vectors. Further, we show that Culicoides vectors believed to be a specialist on specific vertebrate groups can have plastic feeding preferences, and that Culicoides are susceptible to infection by Plasmodium parasites, though vector viability must still be experimentally demonstrated.